20 years of German unification: Evidence on income convergence and heterogeneity - Tilman Brück; Heiko Peters (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2009)
We analyse the convergence and heterogeneity of living standards between East and West Germany since unification. Based on data from the German Socio-Economic Panel (GSOEP), we compare total individual income of permanent adult residents, including retirees and the unemployed, of East and West Germany over the fifteen years for which data are available. Using a fixed effects vector decomposition method, we estimate the gross total income difference between East and West Germans taking unobserved heterogeneity into account. Our analysis demonstrates that the negative income gap has decreased from 33 per cent in 1992 to 22 per cent in 2002, rising again to 26 per cent in 2007. Hence some convergence took place in nominal terms since unification. Constructing income gaps by decennial cohorts, we discover that the most recent cohorts have the highest negative income gap. This probably reflects out-migration from East Germany by the young and highly skilled. On the basis of quantile regressions we find a positive income gap at the beginning of the 1990s for the lower income deciles (that is higher incomes in East Germany). This was due to retirees in the East with relative long employment histories receiving transfer payments by western standards. The income gap is insignificant when accounting for heterogeneity at the area level by including area level variables to our regression.
Keywords: D31; I31; P23; 330; unification; living standards; income inequality; distribution; GSOEP; Germany